Add up all integers x that don't satisfy the below equation.
x − 9 x − 2 = x − 9 x − 2
Note:
This problem is a part of <Don't make mistakes!> series .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I f x − 9 x − 2 < 0 , o r x − 9 = 0 , w e d o n o t h a v e a r e a l s o l u t i o n . x − 9 x − 2 = 1 + x − 9 7 . ∴ o b v i o u s l y , n o s o l u t i o n f o r x = 9 . 1 + x − 9 7 < 0 i f x − 9 7 < − 1 . p o s s i b l e f o r x = 3 , 4 , 5 , 6 , 7 , 8 . S o t h e r e q u i r e d s u m = n = 3 ∑ 9 n = 2 ( 3 + 9 ) ( 8 − 3 + 1 ) = 4 2 .
Problem Loading...
Note Loading...
Set Loading...
We know that b a = − b a only when a ≥ 0 and b < 0 .
Then, the equation won't hold if x − 2 > 0 and x − 9 < 0 , since if x − 2 = 0 , the equation holds.
2 < x < 9 .
So is the answer 3 + 4 + 5 + 6 + 7 + 8 = 3 3 ?
No, we should remember that if x − 9 = 0 , the equation itself doesn't make sense.
Therefore we should include the case x = 9 .
.
The answer is 3 + 4 + 5 + 6 + 7 + 8 + 9 = 4 2 .